EDUCATION BEYOND RATIONALITY - Milčinski, Maja (Journal of Dharma, 2006)
What kind of education are we able to transmit to the children if we ourselves do not engage in some kind of spiritual training which would enable us to embrace life in all its manifestations and provide us with necessary flexibility for survival and growth through various crises, setbacks, illnesses, etc., which represent important tests of our daily living? From the perspective of the so-called socialist ethical orientation, which was dominant in various countries of the 20th century, I will try to show how such one-dimensionality as a by-product of an ideology might be transcended by insights of Asian spiritual traditions, which might help to provide tools for the young people in the search of their own way and the generation of their own well-being also in the times of crises which are necessary part of the growing up process.